Consumption of Alcopops During Brain Maturation Period: Higher Impact of Fructose Than Ethanol on Brain Metabolism - El Hamrani, Dounia; Gin, Henri; Gallis, Jean-Louis; Bouzier-Sore, Anne-Karine; Beauvieux, Marie-Christine (Frontiers in Nutrition, 2018)
Alcopops are flavored alcoholic beverages sweetened by sodas, known to contain fructose. These drinks have the goal of democratizing alcohol among young consumers (12-17 years old) and in the past few years have been considered as fashionable amongst teenagers. Adolescence, however, is a key period for brain maturation, occurring in the prefrontal cortex and limbic system until 21 years old. Therefore, this drinking behavior has become a raising public health concern. Despite the extensive literature concerning the respective impacts of either fructose or ethanol on brain, the effects following joint consumption of these substrates remains unknown. Our objective was to study the early brain modifications induced by a combined diet of high fructose (20%) and moderate amount of alcohol in young rats by 13C Nuclear Magnetic Resonance (NMR) spectroscopy. Wistar rats had isocaloric pair-fed diets containing fructose (HF, 20%), ethanol (Et, 0.5g/day/kg) or both substrates at the same time (HFEt). After 6 weeks of diet, the rats were infused with 13C-glucose and brain perchloric acid extracts were analyzed by NMR spectroscopy (1H and 13C). Surprisingly, the most important modifications of brain metabolism were observed under fructose diet. Alterations, observed after only 6 weeks of diet, show that the brain is vulnerable at the metabolic level to fructose consumption during late-adolescence throughout adulthood in rats. The main result was an increase in oxidative metabolism compared to glycolysis, which may impact lactate levels in the brain and may, at least partially, explain memory impairment in teenagers consuming alcopops.